A detailed analysis on BUCK converter in different conduction mode - Shakil, Md Shaidul Islam (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2018.